Review of quantitative methods for supply chain resilience analysis - Hosseini, Seyedmohsen; Ivanov, Dmitry; Dolgui, Alexandre (Transportation research. Part E, Logistics and transportation review, 2019)
•We review and classify the major features of models proposed in supply chain resilience.•The analysis is rooted in original concept of resilience capacity.•It introduces a structured analysis based on different levels of capacity resilience.•The gaps and limitations of existing supply chain resilience literature are identified and future research opportunities are suggested. Supply chain resilience (SCR) manifests when the network is capable to withstand, adapt, and recover from disruptions to meet customer demand and ensure performance. This paper conceptualizes and comprehensively presents a systematic review of the recent literature on quantitative modeling the SCR while distinctively pertaining it to the original concept of resilience capacity. Decision-makers and researchers can benefit from our survey since it introduces a structured analysis and recommendations as to which quantitative methods can be used at different levels of capacity resilience. Finally, the gaps and limitations of existing SCR literature are identified and future research opportunities are suggested.